PENGELOLAAN KETERBUKAAN INFORMASI PUBLIK DI BPMP PROVINSI DKI JAKARTA - Dini Agustina; Mirza Ronda; Ridzki Rinanto Sigit (LPMP Provinsi DKI Jakarta, 2026)
Public information disclosure is a fundamental principle of democratic governance; however, its implementation in public institutions continues to face various challenges, particularly regarding the clarity and consistency of information. Previous studies indicate that issues of transparency are not solely related to regulatory compliance, but are also shaped by internal organizational communication processes that influence how information is interpreted and managed. This study aims to analyze the management of public information disclosure as an organizational communication process, with a focus on how public institutions address information equivocality. Employing a qualitative approach with an exploratory case study design, this research was conducted at the Educational Quality Assurance Agency (Balai Penjaminan Mutu Pendidikan/BPMP) of DKI Jakarta Province. Data were collected through observation, in-depth interviews with 13 informants, and document analysis, and were examined using thematic analysis supported by NVivo and communication network analysis using UCINET. The findings reveal that BPMP’s transformation from a non-informative to an informative public institution was achieved through a gradual process of reducing information equivocality, including meaning clarification, standardization of procedures and documents, strengthening internal communication and coordination, strategic leadership roles, and the optimization of communication networks and digital technologies. These results underscore that public information disclosure constitutes a complex and dynamic organizational communication process. This study contributes to the development of organizational communication scholarship in the public sector and offers practical implications for enhancing transparency strategies in public institutions.